Information Provision and Preferences for Education Spending: Evidence from Representative Survey Experiments in Three Countries - Maria Alejandra Cattaneo; Philipp Lergetporer; Guido Schwerdt; Katharina Werner; Ludger Woessmann; Stefan C. Wolter (Institute of Labor Economics (IZA), 2019)
Do differences in citizens' policy preferences hamper international cooperation in education policy? To gain comparative evidence on public preferences for education spending, we conduct representative experiments with information treatments in Switzerland using identical survey techniques previously used in Germany and the United States. In Switzerland, providing information about actual spending and salary levels reduces support for increased education spending from 54 to 40 percent and for increased teacher salaries from 27 to 19 percent, respectively. The broad patterns of education policy preferences are similar across the three countries when the role of status-quo and information are taken into account.
Keywords: H52; I22; D72; D83; 330; policy preferences; cross-country comparison; international cooperation; Switzerland; Germany; United States; education spending; information; survey experiments